A Mischief of Mice: Examining Children's Performance in Single Display Groupware Systems with 1 to 32 Mice - Inkpen, Kori; Balakrishnan, Ravin; Cutrell, Ed (International conference on Human factors in computing systems (CHI 2009), 2009)
Mischief is a system for classroom interaction that allows multiple children to use individual mice and cursors to interact with a single large display [20]. While the system can support large groups of children, it is unclear how children’s performance is affected as group size increases. We explore this question via a study involving two tasks, with children working in group sizes ranging from 1 to 32. The first required reciprocal selection of two on-screen targets, resembling a “swarm” pointing scenario that might be used in educational applications. The second, a more temporally and spatially distributed pointing task, had children entering different words by selecting characters on an on-screen keyboard. Results indicate that performance is significantly affected by group size only when targets are small. Further, group size had a smaller effect when pointing was spatially and temporally distributed than when everyone was concurrently aiming at the same targets.